IMPLEMENTASI NILAI MODERASI BERAGAMA DALAM PERSPEKTIF AL-QURAN DI ERA SOCIETY 5.0 - Ansani; Achmad Abubakar; Muhsin Mahfudz (Jurnal Cakrawala Ilmiah, 2021)
This article aims to examine the implementation of the value of religious moderation in the perspective of the Al-Quran in the era of era society 5.0. Religious moderation in the era Society 5.0. era provides religious narratives that are free of access through technology that is often used by certain groups to make religion an aspiration by imposing that is far from tolerant and fair. Therefore, religious moderation is the basis for strengthening religious understanding in era society 5.0, which needs to have characteristics in accordance with the values ​​of the Al-Quran by strengthen religious understanding that is moderate, tolerant and compassionate. The method used in this research is a qualitative method that uses library research as its approach. The research sources used were obtained from various scientific sources, namely books, journal articles, and various other sources related with research studies. Furthermore, with data analysis techniques in the form of descriptive-analytic, the researcher will analyze the data encounters before presenting it. Readers in the midst of a multicultural society. From the results of the study it was found that there are several moderating values ​​in Al The Al-Quran as a reference that needs to be implemented in the era society 5.0. era to create peace in life in the era society 5.0, era, namely a. fostering the value of balance and justice, b. maintain the value of religious tolerance c . maintain the value of religious harmony d. Spread the value of love.